2012
DOI: 10.35536/lje.2012.v17.i2.a6
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, Income Inequality, and Growth in Pakistan: A Pooled Regression Analysis

Abstract: This study estimates a set of fixed effects/random effects models to ascertain the long-run relationships between poverty, income inequality, and growth using pooled data from eight household income and expenditure surveys conducted between 1992/93 and 2007/08 in Pakistan. The results show that growth and inequality play significant roles in affecting poverty, and that the effect of the former is substantially larger than that of the latter. Furthermore, growth has a significant positive impact on inequality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 18 publications
4
22
0
3
Order By: Relevance
“…This coefficient shows the direct and significant impact of this indicator on the reduction of poverty in Tunisia. Our result is consistent with results of Cheema and Sial (2012); Ravallion and Chen (1996) and Lombardo (2008); Kakwani (2001) and Son (2007); Bourguignon (2003) and Son and Kakwani (2004) as well as Hassan (2015).…”
Section: Ardl Bounds Testing To Cointegrationsupporting
confidence: 92%
“…This coefficient shows the direct and significant impact of this indicator on the reduction of poverty in Tunisia. Our result is consistent with results of Cheema and Sial (2012); Ravallion and Chen (1996) and Lombardo (2008); Kakwani (2001) and Son (2007); Bourguignon (2003) and Son and Kakwani (2004) as well as Hassan (2015).…”
Section: Ardl Bounds Testing To Cointegrationsupporting
confidence: 92%
“…Ncube, Anyanwu and Hausken [33], in their study from 2013, on inequality, growth and poverty in the Middle East and North Africa (MENA), showed that income inequality reduces economic growth and increases poverty in the region. A similar positive relationship was supported by [34] in the case of Pakistan between 1993 and 2008, showing that inequality plays a significant role in increasing the poverty rate.…”
Section: Income Inequalitysupporting
confidence: 57%
“…Overall impact of population shift on poverty reduction appears positive. Cheema and Sial (2012) develop a triangle of poverty, growth and income inequality. Pooled data from eight household surveys of 1992-93 and 2007-08 is used for the study.…”
Section: Literature Reviewmentioning
confidence: 99%